A framework for electronic records management in support of e-government in Kenya. (15th March 2019) - Ambira, Cleophas Mutundu; Kemoni, Henry Nyabuto; Ngulube, Patrick
Abstract : Purpose: This paper is based on the doctoral study conducted in 2016 at the University of South Africa. The purpose of this study was to investigate how the current state of management of electronic records in Kenya facilitates or undermines implementation of e-government with a view to develop a best-practice framework for management of electronic records in support of e-government. Design/methodology/approach: The study used the interpretive research paradigm and adopted qualitative research methodology using phenomenological design. Maximum variation sampling was used to identify the research sample for the study. Findings: The findings established that the general status of management of e-records (MER) in government ministries is inadequately positioned to support e-government; use of e-government in Kenya had grown significantly and more ministries were adopting e-government services; although some initiatives have been undertaken to enhance MER, the existing practices for MER require improvement to ensure they adequately support e-government. Research limitations/implications: The limitations were access to respondents and the challenge of self-reported data. Practical implications: Recommendations and a best-practice framework for managing electronic records in support of e-government have been provided. A proposal for implementation of the recommendations on a priority basis has also been provided. Social implications: The study's contribution to scholarly works and literature in the field resides in its findings and a framework that can be practically adopted for management of e-records in support of e-government. By establishing the nexus between management of e-records and e-government in Kenya, it is hoped that it will provide input to policymakers to consider records managers as key stakeholders in e-government. Originality/value: The originality of this study stems from two aspects: original topic and understudied area.